2020
DOI: 10.1007/s13201-020-01240-0
|View full text |Cite
|
Sign up to set email alerts
|

Application of silver nanoparticles toward Co(II) and Pb(II) ions contaminant removal in groundwater

Abstract: Applications of nanomaterials has recently been of keen interest to researchers. This fascinating drive ensued due to their unique properties such as optical, magnetic, ease of synthesis, large surface area, and tunable surface chemistry and functionalization that are remarkably different from that of the bulk material. In this work, silver nanoparticles were synthesized and characterized using UV–Vis spectroscopy and scanning electron microscopy. The UV–Vis spectra obtained showed absorption peak at 406 nm wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Biogenic nanoparticles have enormous applications, which is why tremendous attention is required by many researchers due to many specific properties such as large surface area, affluence of production, optical, magnetic, tunable surface chemistry and their functions that are different from bulk material [ 171 ]. It was also reported that rGO (reduced grapheme oxide) hybridized with magnetic and/or elemental silver nanoparticles (rGO/magnetite, rGO/magnetite/silver and rGO/silver) is a potential adsorbent for noxious heavy metals such as Cd, Ni, Zn, Pb, Cu, and Co.…”
Section: Silver Nanoparticle In Mitigation Of Heavy Metal Stress In P...mentioning
confidence: 99%
See 1 more Smart Citation
“…Biogenic nanoparticles have enormous applications, which is why tremendous attention is required by many researchers due to many specific properties such as large surface area, affluence of production, optical, magnetic, tunable surface chemistry and their functions that are different from bulk material [ 171 ]. It was also reported that rGO (reduced grapheme oxide) hybridized with magnetic and/or elemental silver nanoparticles (rGO/magnetite, rGO/magnetite/silver and rGO/silver) is a potential adsorbent for noxious heavy metals such as Cd, Ni, Zn, Pb, Cu, and Co.…”
Section: Silver Nanoparticle In Mitigation Of Heavy Metal Stress In P...mentioning
confidence: 99%
“…The observations noted highlights removal effectiveness of 77% and 24% for lead and cobalt, respectively. It is significant to note that the quantity of metal ions decreases with increasing incubation timeframe [ 171 ].…”
Section: Silver Nanoparticle In Mitigation Of Heavy Metal Stress In P...mentioning
confidence: 99%
“…The results showed that cobalt and lead were eliminated with 24 percent and 77 percent efficiency, respectively. It is important to note that when the incubation durations were prolonged, the concentrations of metal ions decreased [ 101 , 102 ]. Ituen et al disclosed the creation of silver nanoparticles from walnut husk extract.…”
Section: Nanomaterials Used For Heavy Metal Removalmentioning
confidence: 99%
“…Particularly, nanomaterials have gained a lot of attention due to their multidimensional use in every field starting from environment to life saving drug molecule synthesis [14,15]. Easy method of preparation, low cost, avoidance of harmful reagents and solvents, high yield, small size with large surface area are the most charming features found to be associated with the nanomaterials which makes them more demandable [16][17][18][19][20]. Among the variety of nanomaterials invented, silver nanoparticles are quite unique and desirable as because of their cost-effective synthesis, environmentally sustainable and most significantly their high toxicity only towards the multidrug resistant micro-organisms over healthy cells and soil at low dose.…”
Section: Introductionmentioning
confidence: 99%